Easy-Erase for Whiteboard Prototype - Shazleen Azwa Khairullah; Kunchi Mon, Siti Zaharah (Progress in Engineering Application and Technology, 2024)
This thesis addresses the need for efficient maintenance of traditional whiteboards in educational and professional settings, proposing an automatic cleaner that integrates advanced technology to streamline the cleaning process, reduce manual effort, and enhance overall efficiency. The study emphasizes the limitations of manual cleaning methods and the adverse health effects of common cleaning agents. Through a detailed design process, the development involves an Arduino Uno microcontroller, motor driver, DC motor, ultrasonic sensor, and push button, with evaluation criteria covering cleaning efficiency, speed, user-friendliness, maintenance, durability, user satisfaction, compatibility, and environmental impact. The mechanism system utilizes smart algorithms and a schematic diagram, demonstrating the device’s ability to navigate and clean thoroughly. Time analysis data confirm the significant reduction in cleaning time compared to manual methods, making the proposed automatic whiteboard cleaner a promising solution for maintaining clean and functional whiteboard surfaces.